Two‐dimensional heterostructure promoted infrared photodetection devices. Issue 3 (8th July 2019) - Rao, Gaofeng; Wang, Xuepeng; Wang, Yang; Wangyang, Peihua; Yan, Chaoyi; Chu, Junwei; Xue, Lanxin; Gong, Chuanhui; Huang, Jianwen; Xiong, Jie; Li, Yanrong
Abstract: It is a rapidly developed subject in expanding the fundamental properties and application of two‐dimensional (2D) materials. The weak van der Waals interaction in 2D materials inspired researchers to explore 2D heterostructures (2DHs) based broadband photodetectors in the far‐infrared (IR) and middle‐IR regions with high response and high detectivity. This review focuses on the strategy and motivation of designing 2DHs based high‐performance IR photodetectors, which provides a wide view of this field and new expectation for advanced photodetectors. First, the photocarriers' generation mechanism and frequently employed device structures are presented. Then, the 2DHs are divided into semimetal/semiconductor 2DHs, semiconductor/semiconductor 2DHs, and multidimensional semi‐2DHs; the advantages, motivation, mechanism, recent progress, and outlook are discussed. Finally, the challenges for next‐generation photodetectors are described for this rapidly developing field. Abstract : The strategy and mechanism of designing 2D heterostructures based high‐performance infrared photodetectors with high response and high detectivity as well as broadband range are systematically reviewed, which provides a wide view of this field and new expectation for advanced photodetectors.